Stroke drills - Richards, R. (1999)
Stroke drills are teaching/learning applications which try to isolate some aspect of stroke technique to develop new, or more consistent, movement patterns. There are an infinite number of drills that a coach could use. The drills presented here are but a few examples and are not meant to be comprehensive list. The drills here include: - Sculling Drills, - freestyle and backstroke drills, - breaststroke drills, - butterfly Drills (both with and without fins).